Comparison of race time-differences between and within para and able-bodied cross-country skiers - Carlsen, C. H.; Severin, C.; Sandbakk, Ø.; Baumgart, J. K. (Frontiers in Sports and Active Living, 2022)
Purpose: To compare differences in race time (i.e., the average percent difference in race time for each skier compared to the winner, RTdiffs) between female and male Para and able-bodied (AB) skiers, and to examine whether RTdiffs change across seasons.